Do Enterprise Risk Assessments Affect Tax Aggressiveness? Evidence from U.S. ORSA Regulation - Krupa, Trent J. (The Accounting Review, 2024)
ABSTRACT Tax aggressiveness presents nontax risks to firms’ cash flow. Evaluating these risks requires information beyond the accounting function’s expertise, resulting in high processing costs to acquire and integrate risk information relevant to tax strategies. Managers can rationally adapt by making assumptions about risk information, potentially resulting in decision biases when evaluating the risk-reward tradeoff of tax aggressiveness. Using a novel regulatory setting in the U.S. insurance industry, I examine whether the adoption of mandated enterprise risk assessments updates managers’ prior beliefs about the nontax risks of tax aggressiveness. I find that as regulation requires managers to accept processing costs to acquire and integrate risk information, managers learn about previously underestimated nontax risks and significantly reduce tax aggressiveness. Results suggest that absent firm-wide internal risk information, managers can use aggressive tax positions without fully considering nontax risks. Data Availability: Data used in this study are available from public sources identified in the paper. JEL Classifications: G22; G32; H25; M41.